Bulk nanostructured materials : fundamentals and applications - 376090 Valiev, Ruslan Z.; Zhilyaev, Alexander P.; Langdon, Terence G. (Hoboken, NJ. : John Wiley & Sons, Inc,-TMS, 2013)
Includes bibliographical references and index.